Natural history of tinnitus in adults: a cross-sectional and longitudinal analysis - Piers Dawes; David Stockdale; David M Baguley; John Newall (BMJ Open, 2020)
Objective To assess incidence and changes in tinnitus and bothersome tinnitus as well as associated risk factors in a large sample of UK adults.Design Prospective cohort study.Setting UK.Participants For cross-sectional analysis, a group of 168 348 participants aged between 40 and 69 years with hearing and tinnitus data from the UK Biobank resource. Longitudinal analysis included a subset of 4746 people who attended a 4-year retest assessment.Main outcome measures Presence and bothersomeness of tinnitus.Results 17.7% and 5.8% of participants reported tinnitus or bothersome tinnitus, respectively. The 4-year incidence of tinnitus was 8.7%. Multivariate logistic regression models suggested that age, hearing difficulties, work noise exposure, ototoxic medication and neuroticism were all positively associated with both tinnitus and bothersome tinnitus. Reduced odds of tinnitus, but not bothersome tinnitus, was seen in alcohol drinkers versus non-drinkers. Male gender was associated with increased odds of tinnitus, while female gender was associated with increased odds of bothersome tinnitus. At follow-up, of those originally reporting tinnitus, 18.3% reported no tinnitus. Of those still reporting tinnitus, 9% reported improvement and 9% reported tinnitus becoming more bothersome, with the rest unchanged. Male gender and alcohol consumption were associated with tinnitus being reported less bothersome, and hearing difficulties were associated with the odds of tinnitus being reported as more bothersome.Conclusions This study is one of the few to provide data on the natural history of tinnitus in a non-clinical population, suggesting that resolution is relatively uncommon, with improvement and worsening of symptoms equally likely. There was limited evidence for any modifiable lifestyle factors being associated with changes in tinnitus symptoms. In view of the largely persistent nature of tinnitus, public health strategies should focus on: (1) primary prevention and (2) managing symptoms in people that have tinnitus and monitoring changes in bothersomeness.